Relevance development of project culture teachers of vocational training in innovative progress society - Svitlana Kravec (Vasyl Stefanyk Precarpathian National University, 2018)
The article announced the relevance of project culture teacher training; the essence of the concept of «project culture of the teacher of vocational training»; delineated tasks of scientific research, implementation of which will facilitate the achievement of positive dynamics in improving the indicators of project culture teachers professional training in the innovative development of society. Keywords: project culture, teacher of vocational training, vocational education.